Experiences of Juveniles Offenders Before and During Their Stay in Rehabilitation Homes: A Case of Naguru Remand Home - Maria Gabriella Apolot (Uganda Christian University, 2024)
The purpose of this study was to examine the experience of juvenile offenders before and after during their stay at Naguru Remand Home. The study was carried out in government rehabilitation/remand Naguru Remand Home. Specifically, the study sought to examine determinants of the juvenile’s behaviors, assess the various services provided to the juveniles at Naguru remand home and to explore the experiences of juvenile at Naguru remand home. The study consisted of a total population of 168 juveniles. Out of this, the study selected a sample size of 20 respondents. The data for the study was collected using interview schedules, and observation. After data collection, it was analyzed qualitatively then presented in tables, figures and prose form. The study found out that the rehabilitation center had majority of male juveniles compared to female counterparts. Many of the Juveniles were in remand home because of crimes they committed. Most juveniles were living with their parents and few living with their guardians before coming to remand homes. The study recommended that the stakeholders should put the necessary efforts to make living conditions more favorable for the children and remand home facilities should be provided to cater for juveniles in remand homes.
Undergraduate research